استحداث محطات الصرف الصحي المنزلية و استخدام مياه المعالجة الناتجة منها في سقي بعض المزروعات - خالد سهيلة; الأبرق سمية (جامعة الوادي - university of eloued, 2024)
with the aim of preserving water resources and solving the problem of sewage discharge in remote areas not connected to the public sewage network. we have established a domestic wastewater treatment plant, which converts liquid waste resulting from household uses into water suitable for agricultural use. this study was conducted during the agricultural season 2023-2024 ad, at the “Tayba” foundation in the municipality of al-Bayada - al-Oued - where the treatment plant was integrated with the domestic sewage system for the workers’ housing of this institution. we also supported this station with an electric air pump to supply it with oxygen, as well as adding bacteria. to activate interactions within this station. physical and chemical microbiological analyzes were also conducted on treated water samples according to approved methods. to evaluate the suitability of this water for irrigation, we conducted an agricultural experiment for bean and zucchini crops. the experiment was divided into two groups according to the quality of the irrigation water used: treated domestic sewage water and regular water. we also studied the effect of the quality of the water used on the various stages of growth and development of the studied plants. which showed positive results in the use of treated water for irrigation, as most of the elements were within the permissible standards and other elements were fluctuating in their concentration due to the beginning of the plant’s stability in treatment. hence, it can be said that this station is capable of producing water suitable for agricultural use and safe for the environment.
إنتاج نباتي
Keywords: treatment plant; water resources; sewage system; heavy metals; microbiological; physical; chemical; suspended materials; treated domestic wastewate